Bilateral Vesicoureteric Reflux may be a Rare Association in Lesch-Nyhan Syndrome: A Case Report (Bangladesh Journal of Child Health, 2017)
Abstract not availableBangladesh J Child Health 2016; VOL 40 (1) :44-48